Comprehensive Analysis of the Expression and Prognosis for ITGBs: Identification of ITGB5 as a Biomarker of Poor Prognosis and Correlated with Immune Infiltrates in Gastric Cancer - Liu, Dongliang; Liu, Shaojun; Fang, Yu; Liu, Liu; Hu, Kongwang (Frontiers in Cell and Developmental Biology, 2022)
Background Integrin β superfamily members (ITGBs) had been documented to play important roles in various biological processes, and accumulating evidence suggested that ITGBs were associated with carcinogenic effects in several malignancies. Gastric cancer (GC) is a complicated and highly heterogeneous disease, however, the expression and prognostic values of eight ITGBs and potential mechanism in GC remain largely unclear. Methods The expression and prognostic significance of ITGBs in GC were systematically analyzed through Gene Expression Profiling Interactive Analysis (GEPIA), Human Protein Atlas, Kaplan-Meier Plotter, and cBioPortal databases. And then the mRNA transcription data and corresponding clinical data of GC were downloaded from Gene Expression Omnibus (GEO) database as a testing cohort, and differentially expressed and prognostic genes were identified. The correlation between ITGB5 expression and overall survival (OS), and various clinical parameters by using univariate/multivariable Cox regression and Kaplan-Meier survival analysis. Additionally, differential analysis of gene expression profiles in low- and high-ITGB5 expression groups and pathway enrichment analysis were performed. Finally, the correlation of ITGB5 expression with immune infiltrates in GC was clarified. Results Compared with adjacent normal tissue, the results reveal that the mRNA levels of ITGB1-2 and ITGB4-8 were significantly higher in GC, and the IHC results showed the consistency between RNA and protein expression levels. Cox regression and Kaplan-Meier survival analysis indicated that high ITGB5 expression contributed to a poor prognosis, and could be an independent prognostic factor in GC patients. Besides, gene functional enrichment analysis indicated that ITGB5 expression is significantly associated with extracellular matrix organization, cell-substrate adhesion and ossification. The KEGG pathway analysis of ITGB5 showed a close association between ITGB5 and focal adhesion, ECM-receptor interaction, phagosome and PI3K-Akt signaling pathway. Lastly, the infiltrating level of CD4+ T cells, macrophages and dendritic cells were positively related to the expression of ITGB5, especially macrophages, and the lower level of macrophages predicted a better prognosis in GC in our study. Conclusion Our findings investigated that ITGB5 may function as a valid biomarker of prognosis and high expression of ITGB5 predicts poor prognosis for patients with GC. Besides, it might be a potential target of precision therapy against GC.